Genetic characterization of the Aphyosemion calliurum species group and description of a new species from this assemblage: A. campomaanense (Cyprinodontiformes: Aplocheiloidei: Nothobranchiidae) from Southern Cameroon - Agnèse, Jean-François; Brummett, Randall; Caminade, Pierre; Catalan, Josette; Kornobis, Etienne (Zootaxa, 2009)
The Aphyosemion calliurum species group is poorly diagnosed by chromatic and meristic characteristics leading various authors to propose different species as members. We used partial sequence of the mitochondrial cytochrome b gene to characterize all species that have been at one time or another included in the A. calliurum species group. Results obtained allowed a clear definition of the group which is composed of 10 species: A. ahli, A. australe, A. calliurum, A. celiae, A. edeanum, A. franzwerneri, A. heinemanni, A. lividum, A. pascheni, and a herein newly described species A. campomaanense. This new species is described from 26 specimens captured in small streams of the Campo-Ma’an region within the Ntem River basin of southern Cameroon. A. campomaanense n. sp. is distinguished from all the other species of the A. calliurum species group, and above all from A. ahli, by asymmetric coloration of the caudal fin with a yellow lower margin and a white upper margin, and a body with a dark blue background against which red spots are arrayed in horizontal rows towards the head merging into vertical rows posteriorly. This species is also genetically distinguished from the other species of the A. calliurum species group by its mitochondrial genome and its karyotype, characterized by an unusually high number of chromosomes and arms (2n= 44, NF=58).